The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3389/fcimb.2016.00192
|View full text |Cite
|
Sign up to set email alerts
|

The Preferential Infection of Astrocytes by Enterovirus 71 Plays a Key Role in the Viral Neurogenic Pathogenesis

Abstract: The pathological manifestations of fatal cases of human hand, foot, and mouth disease (HFMD) caused by enterovirus 71 (EV71) are characterized by inflammatory damage to the central nervous system (CNS). Here, the dynamic distribution of EV71 in the CNS and the subsequent pathological characteristics within different regions of neonatal rhesus macaque brain tissue were studied using a chimeric EV71 expressing green fluorescence protein. The results were compared with brain tissue obtained from the autopsies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 39 publications
6
35
0
Order By: Relevance
“…First, virus replication in brain cells may be restricted. This is supported by histopathological studies showing very few neurons in brain are infected with EV-A71 [59, 60]. EQI viruses failed to acquire the VP1-K244E mutation, presumably due to lower infectivity of neurons and suboptimal replication following direct inoculation into brain, resulting in low virulence in mice.…”
Section: Discussionmentioning
confidence: 90%
“…First, virus replication in brain cells may be restricted. This is supported by histopathological studies showing very few neurons in brain are infected with EV-A71 [59, 60]. EQI viruses failed to acquire the VP1-K244E mutation, presumably due to lower infectivity of neurons and suboptimal replication following direct inoculation into brain, resulting in low virulence in mice.…”
Section: Discussionmentioning
confidence: 90%
“…In fatal cases of EV-A71, the viral antigen was detected by histology within neurons and astrocytes (Yan et al, 2000;Yu et al, 2014). Similarly, post-mortem brain tissues from patients with confirmed EV-A71 infection and brain tissue from a non-human primate model of EV-A71 revealed that more than 80% of EV-A71 antigen was detected in astrocytes (Feng et al, 2016). As EV-D68 infected hiPSC derived astrocytes produced 2x more virus within 24 h post infection than 3 days post infection in neurons , it suggests that glia may be important for rapid viral propagation within the CNS.…”
Section: Cns Cell Types Susceptible To Enterovirusesmentioning
confidence: 95%
“…As EV-D68 infected hiPSC derived astrocytes produced 2x more virus within 24 h post infection than 3 days post infection in neurons , it suggests that glia may be important for rapid viral propagation within the CNS. Further in vitro functional studies identified that EV-A71 infected astrocyte cultures released pro-inflammatory cytokine IL-6 which increased secretion of excitatory neurotransmitters in bystander neurons that could have profound consequences on neuronal function (Feng et al, 2016) and immune response within the CNS. Collectively, this data highlights the important role astrocytes play in the development of neurological complications observed during EV infection.…”
Section: Cns Cell Types Susceptible To Enterovirusesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a selective barrier, blood-brain barrier (BBB) protects central nervous system (CNS) from harmful pathogens in the blood. The access of EV-A71 into the CNS, except via retrograde axonal transport by nerves, most likely occurs through the BBB (Feng et al 2016). As a neurotropic virus, the mechanisms by which EV-A71 crossing the BBB and disseminating into brain parenchyma remain largely enigmatic (Denizot et al 2012).…”
Section: Introductionmentioning
confidence: 99%